(untitled) (The Pakistan Development Review, 2003)
Trade and growth theories generally predict a positive relationship between openness to international trade and economic growth. There are a number of channels through which openness is thought to influence economic growth. First, a liberal trade regime enhances efficiency through greater competition and improved resource allocation. Second, greater access to world markets allows economies to overcome size limitations and benefit from economies of scale. Third, imports of capital and intermediate goods can contribute to the growth process by enlarging the productive capacity of the economy. Fourth, trade can lead to productivity gains through international diffusion and adoption of new technologies. Empirical studies on the relationship between openness and economic growth have largely supported the view that openness has a favourable impact on economic growth. It is not surprising, then, that the proposition that more open economies tend to grow faster has gained wide acceptance in academic as well as policy circles. The objective of this paper is to examine the relationship between openness and economic growth in the context of Pakistan’s economy. Section 2 reviews the literature on openness and economic growth. Section 3 provides an overview of trade liberalisation in Pakistan. Data and methodology are described in Section 4, while Section 5 presents the empirical results. Section 6 concludes the discussion.